RACISM MANIFESTED IN A FILM ENTITLED THE HURRICANE - RAHAYU, MARGANING SULISTYO (Jurnal Ilmiah Mahasiswa FIB, 2013)
Racism is the crucial issue in this world and has become a problem sincehundreds of years ago. The colonialist who came to America believes that blackpeople are inferior caste in society. This construction is used to legitimize theenslavement of blacks. This leads to the oppression of the whites toward theblacks. As human beings the blacks have no rights to live in freedom andprosperity. In society, they have a lower position than the whites. In contrast ofthe white still have a higher position than the competent black person. Racialbiases against blacks are still apparent today through many different areas of thecriminal justice system. The black Americans argue that they are treatedunequally and more brutally than the whites at all levels in the criminal justicesystem as it is portrayed in a film entitled The Hurricane. It is a true story movietells about an African-American boxer named Rubin “Hurricane” Carter. Afterfacing all discrimination, racial injustice and unfair law system with a worstverdict, Rubin is free from the accusation that he killing three white people. Related to the issue of racism occurs in the movie, Postcolonial theory play arole here to see the relationship between various aspect in life such as social,political, intellectual, psychological, and especially in the case of law. In racism,the whites limit the black people‟ lives so they ha ve no freedom in their own life.It is the different skin color that makes the blacks got different treatments whichtend to be negative from the whites. Racist attitudes are considered as laws,religion, and everyday practice which influence all of the aspects of life. As it isshown in the movie, Rubin had many obstacles in his life since he was a kidcaused by racial discrimination. The racial discrimination is maintained by whitesupremacy to control their power and to eliminate the opportunity for coloredpeople. This research result (1) Many conflicts in it are the result of prejudice anddiscrimination against blacks and portrayed through such ways as personal life,legal law, appearance, and even the setting and the assumption of the distinctionbecomes crucial. (2) The physical appearance becomes the most important factorin this movie. Racism usually stems of ignorance. It its the assumption that thecolor of one‟s skin has something to do with intelligence. Keywords: racism, film, The Hurricane